Management of proximal tibial stress fracture associated with advanced knee osteoarthritis: A systematic review - Mukesh Kumar Saini; Mahendra Singh; Devendra Singh; Prem Manohar Seervi; Pera Jayavardhan Reddy; Neelam Ramana Reddy (Chinese Journal of Traumatology, 2024)
Purpose: Tibial stress fracture associated with knee osteoarthritis is an unusual and difficult clinical scenario. There is no clear existing treatment guideline for this uncommon clinical disease. The aim of this study is to review the impact of various treatment options for patients with advanced knee osteoarthritis associated with proximal tibial stress fracture. Methods: The study was performed using the databases of PubMed and Scopus. Methodological index for non-randomized studies score was used to evaluate the included studies’ bias. The concluded data included the treatment approach, reported outcome measure, and time to fracture union. The literature search was started in December 2021 and accomplished in January 2022. A narrative description of the different methods and comparison of their results were done. Results: Out of total assessed 69 studies, 9 studies were included in our review. The commonest treatment approach used was total knee arthroplasty by long tibial stem extension. The mean preoperative knee society score and knee functional score were 30.62 and 23.17, respectively. The mean postoperative knee society knee score was 86.87, while the functional score was 83.52. The average reported time to achieve fracture union was 4 months (a range of 2.07 – 5.50 months). Conclusion: The optimal clinical outcome for treating either acute or mobile tibial stress fracture in patients with advanced knee osteoarthritis can be achieved with long stem total knee arthroplasty. However, due to heterogeneity of data, comparison of different treatment options for chronic proximal tibial stress fracture mal-union/non-union coexisting with knee osteoarthritic and such inferences need to be judged cautiously.